Education in rural popular movements: state of the art (2016)
The academic literature on social movements is characterized by a course that started in the US and European academies in the sixties-seventies and arrived strongly in Latin America in the decades of the eighties and nineties. In our region, this category suffers a semantic displacement towards the notion of popular movement in the light of the experiences of resistance to neoliberalism. Thus, new lines of inquiry were opened; the standing out subject area deals with the link between popular movements and education by understanding that political practices are inseparable from teaching practices. This paper reviews the leading academic works on rural popular movements and education developed in Argentina and Brazil and sorts them into three categories according to the type of space-time targeted: schools spawned and driven by movements; the movement as a subject and formative principle; and finally workshops created for training purposes on various topics related to political mobilisation. The aim of the article is to contribute support and substance to an innovative and developing academic area and to emphasize the centrality of rural educational experiences to research about this subject and therefore not to be omitted.